Improving tool life using cryogenic cooling - Khan, Ahsan Ali; Ahmed, Mirghani Ishak (Elsevier, 2008)
The major needs in machining are high material removal rate, good work surface finish and low tool wear. These objectives can be achieved by reducing tool wear using proper cooling system of the tool during machining. In the present work a tool has been modified to apply liquid nitrogen as coolant through a hole made in the tool so that liquid nitrogen can be directly applied to the machining zone during machining of stainless steel with carbide tools coated with titanium carbonitride. It was found that the tool life increases more than four times by applying liquid nitrogen using the modified tool. Application of this cryogenic cooling was found to be more effective at higher cutting speeds. It was also observed that cryogenic cooling is efficient at a higher feed rate rather than a higher depth of cut.